Internalisasi Kearifan Lokal Leva Nuang Sebagai Penguatan Pendidikan Karakter Dalam Pembelajaran IPAS di Sekolah Dasar - Erwin Simon Paulus Olak Wuwur; Dedi Kuswandi; Siti Awaliyah (Jayapangus Press, 2023)
Local wisdom plays an important role in instilling character in students. However, appreciation of local wisdom is still very minimal. This study aims to strengthen the awareness of elementary school students towards positive values ​​in their lives. This effort aims to improve the character of students so that they are able to maintain harmonious relationships with fellow human beings and the environment through daily actions that reflect good values. A descriptive qualitative methodology was used in this study. Data collection techniques through observation, in-depth interviews and documentation. The findings in this study are that leva nuang local wisdom has values ​​that form the basis of aspects of human life such as values ​​of life, socio-culture, knowledge, ethics and social life. There are values ​​that are implemented in learning, namely the values ​​of togetherness, religion, responsibility, democracy, communication and cooperation or mutual cooperation. In science lessons, these values ​​become a source of student learning. Achievement of internalization of religious attitudes and student responsibility in learning is achieved in the good category. The presence of local wisdom in the school curriculum supports the achievement of internalization.